1996
DOI: 10.1007/s002689900084
|View full text |Cite
|
Sign up to set email alerts
|

Pancreaticobiliary Maljunction‐Associated Pancreatitis: An Experimental Study on the Activation of Pancreatic Phospholipase A2

Abstract: Congenital dilatation of the bile duct (CDBD), or choledochalcyst, is often complicated by recurrent pancreatitis. Reflux of pancreatic juice into the bile duct through pancreaticobiliary maljunction (PBM), an anomaly commonly associated with CDBD, and ensuing activation of pancreatic enzymes could be involved in the pathophysiologic mechanism of recurrent pancreatitis. A study was undertaken to follow the time course of the activity of phospholipase A2 (PLA2) in animal models of PBM. The assay procedures for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 40 publications
0
22
0
Order By: Relevance
“…The etiology of pancreatitis in children is varied, and the recurrent form is mostly associated with congenital etiology, such as dilatation of the bile duct combined with pancreaticobiliary maljunction, pancreas divisum, intrapancreatic duplication of the intestine, and so on [1][2][3][4][5]. However, malrotation of the intestine has been reported as a very rare cause of recurrent pancreatitis [6].…”
Section: Introductionmentioning
confidence: 97%
“…The etiology of pancreatitis in children is varied, and the recurrent form is mostly associated with congenital etiology, such as dilatation of the bile duct combined with pancreaticobiliary maljunction, pancreas divisum, intrapancreatic duplication of the intestine, and so on [1][2][3][4][5]. However, malrotation of the intestine has been reported as a very rare cause of recurrent pancreatitis [6].…”
Section: Introductionmentioning
confidence: 97%
“…A frequent association of biliary tract carcinoma and APBDU is well recognized [12][13][14][15][16][17][18][19] , especially in the undilated type APBDU [20,21] . Mori [7] had reported that among 698 patients subjected to endoscopic retrograde cholangiopancreatography, APBDU was found in 6 patients (0.9 %).…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the activation of pancreatic enzymes by bile reflux, 31 in association with an anomalous pancreaticobiliary union. Certainly, the anomalous ductal union seems to predispose to pancreatitis, as in one study, 57% of patients with choledochal cysts had anomalous ductal union demonstrated by ERCP.…”
Section: Complications Pancreatitismentioning
confidence: 99%
“…The high incidence of anomalous pancreaticobiliary union cannot be ignored, but may just reflect an association with distal obstruction. Alternatively, pancreatic juice reflux into the common bile duct may be activated by bile, 31 and activated enzymes subsequently weaken the common bile duct wall, exacerbating the dilatation.…”
Section: Etiologymentioning
confidence: 99%